'Mateur' and 'Ohadi' cultivars characteristics over fifteen years of production in Sfax semi-arid region - Ghrab M.; Gouta H.; Ben Mimoun M. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
Pistachio-tree performance of two female cultivars, a local one 'Mateur' (the most important cultivar in Tunisia) and a foreign one 'Ohadi' (an Iranian cultivar), has been studied in Sfax region. The yield per tree of each cultivar was analysed regarding the climatic conditions, especially rainfall, during a period of fifteen years. The flowering period and production characteristics (weight, shell dehiscence and size) were also monitored. The results show important differences between the two cultivars under the semi-arid conditions of Sfax region.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)